Caring for Thailand’s Aging Population - Glinskaya, Elena; Walker, Thomas; Wanniarachchi, Thisuri (World Bank, Washington, DC, 2021)
Thailand is the second-fastest aging country in the Association of Southeast Asian Nations (ASEAN) after Singapore, and it is growing old before it grows rich. Thailand has already made considerable progress in recognizing the ageing challenge and has initiated policy reforms and development programs to address it at both national and local levels. The 2012–16 National Economic and Social Development Plan and, more recently, the 2017–2036 National Strategy, underscore the welfare of older persons as a government priority. At the heart of Thailand’s approach is universal health insurance, supported by a community-based primary health care system with a reliance on volunteers. Thailand is now working to expand access to long-term care (LTC) at the community level as part of this volunteer-supported primary health care system. This report was prepared based largely on secondary sources, given the limitations on travel during 2020. It makes use of the comprehensive results of the Survey of Older Persons in Thailand, as well as excellent studies produced by various government, non-government, and academic authors. Nevertheless, in preparing the report the authors noted considerable data gaps, especially on private sector services, costs and usage, labor force, and projections of future demand for care. The team fact-checked the report with various country and sector experts; however, it should be considered a preliminary overview of the current situation. Additional data and consultation are needed to elaborate on the recommendations provided in this report.